Лінгвістичне буття лексем "about", "round" - Semeniuk, Antonina A.; Семенюк, Антоніна Афанасіївна (Сумський державний університет, 2013)
У статті розглядаються етимологічні витоки класифікації частин мови на самостійні та службові й особливості будови і функціонування прийменників залежно від контексту їх уживання. The article deals with the etymological sources of parts of speech classification into functional and structural ones, besides both structural and functional peculiarities of prepositions are considered depending on the context of their usage.
Linguistic being of lexemes “about”, “round”
Keywords: preposition; прийменник; functional word; самостійне слово; evolution; еволюція; structural word; службове слово